Psychometric properties of the Youth Anxiety Measure for DSM-5 (YAM-5) in a community sample. (1st October 2017) - Simon, Ellin; Bos, Arjan E.R.; Verboon, Peter; Smeekens, Sanny; Muris, Peter
Abstract: To detect children with dysfunctional levels of fear and anxiety, we need reliable and valid measures that fit the contemporary diagnostic system and suit and support current practices in mental health. Therefore, we developed the Youth Anxiety Measure for DSM-5 (YAM-5), a questionnaire that assesses symptoms of the full range of the contemporary anxiety diagnoses of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Part I of the YAM-5 measures all of the major anxiety disorders and Part II measures all of the specific phobias. The current study evaluated the psychometric properties of the child self-report version of the YAM-5. Children ( N  = 414) aged 8 to 12 years ( M  = 10.49, SD  = 1.04) were recruited via regular primary schools and the data were collected at school during regular classes. Good internal consistencies were demonstrated for the subscales of Part I and for the total scale of Part I and Part II. Furthermore, good test-retest reliability, good concurrent validity and good construct validity of both parts of the questionnaire were found. Overall, this study strongly indicates that the YAM-5 is suitable for measuring symptoms of anxiety disorders in community samples. Highlights: Overall good internal consistency of the YAM-5 Good test-retest reliability of the YAM-5 Good concurrent validity of the YAM-5 Good construct validity of the YAM-5 The YAM-5 is suitable for measuring anxiety symptoms in community samples.